Monetary Policy Transmission and Financial Stability in a LIC : The Case of Bangladesh - Rafiq, Sohrab (Washington, D.C. : International Monetary Fund, 2015)
This paper explores how monetary policy affects the real economy and its efficacy in promoting financial stability in a large low income country. This paper shows that monetary policy modestly impacts real economic activity and inflation via the bank lending and financial accelerator channels. Second, money market and treasury rates signal changes in the policy stance, while altering banks' intermediation cost curves due to shifting risk premia. At the same time, evidence points to monetary policy inducing an overshooting in asset prices. These findings suggest that financial stability could be undermined if the calibration of monetary policy is based solely on output and inflation without accounting for the stage of the financial cycle. Finally, the paper discusses policy measures that would enhance the transmission of monetary policy and promote financial stability in Bangladesh.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet